Review paperBladder preservation with brachytherapy compared to cystectomy for T1-T3 muscle-invasive bladder cancer: a systematic review - Bos, Manouk K.; Marmolejo, Rafael Ordońez; Rasch, Coen R.N.; Pieters, Bradley R. (Journal of Contemporary Brachytherapy, 2014)
Purpose: Radical cystectomy currently is the treatment of choice in muscle-invasive bladder cancer. However, cystectomy is associated with considerable morbidity. Bladder sparing treatment consists of transurethral resection of the tumor (with or without partial cystectomy), external beam radiotherapy, and brachytherapy. The purpose of this study is to compare bladder preservation with brachytherapy to cystectomy by a systematic review. Material and methods : A systematic review was conducted using PubMed electronic database. Article selection was done independently by two authors. Data were extracted on cause-specific survival and overall survival at 2, 5, and 10 years. Comparison of the two treatment modalities was done by a Weibull survival analysis with metaregression analysis and estimation of Hazard Ratio’s (HR’s) with 95% confidence intervals (CI). Results : Large differences in tumor staging and tumor grading were found between cystectomy and bladder sparing series. The adjusted HR’s for cause-specific survival and overall survival were 1.27 (95% CI: 1.15-1.40) and 0.85 (95% CI: 0.84-0.87), respectively for bladder sparing relative to radical cystectomy. Conclusions : Robustness of the analysis is hampered by the retrospective character of the study and differences in patient characteristics. For selected cases, bladder sparing by brachytherapy leads to at least similar overall survival compared to radical cystectomy for muscle invasive bladder cancer.